Carbon ion beam dosimetry in magnetic fields using Farmer-type ionization chambers of different radii: measurements and simulations - Surla, Sonja; Marot, Mathieu; Burigo, Lucas Norberto; Brons, Stephan; Runz, Armin; Karger, Christian (Physics in medicine and biology, 2024)
Objective. To investigate magnetic field effects on the dose distribution and ionization chambers response in carbon ion reference fields and determine magnetic field correction factors for chambers of different volumes. Approach. The response of six Farmer-type chambers with varying radii (1-6 mm, termed as R1-R6) was measured in magnetic fields up to 1 T in 0.1 T increments using an experimental electromagnet and compared with Monte Carlo simulations. Chamber readings were measured in the entrance region of a monoenergetic carbon ion beam of 390.75 MeV u−1. A lower energy of 200.28 MeV u−1 was applied to chamber R3 for comparison. Polarity and recombination corrections were investigated for the R3 chamber. The local dose change induced by the magnetic field was calculated by Monte Carlo, which together with change of the chamber’s response, was used to calculate the final magnetic field correction factors. Main results. The dependence of the chamber response on the magnetic field was non-linear and volume-dependent. Maximum changes ranged from 0.30% (R4) to 0.62% (R5) at 0.2 T. For R3, the response for the lower energy was systematically decreased by 0.2% in the range of 0.2 T to 0.7 T. No significant effect of the magnetic field on polarity and ion recombination correction was found. The maximum variation of the local dose was found to be (0.03 ± 0.08) % at 0.2 T for beam energy of 390.75 MeV u−1. Magnetic field correction factors for the different chambers ranged from 0.28% (R4) to 0.60% (R5). Significance. This study provides the first detailed analysis of chambers’ response to magnetic flux densities of up to 1 T using chambers of different radii and comparison with simulations. By combining the chamber response alterations with local dose changes magnetic field correction factors were calculated for all six chambers, including the commercial Farmer-type chamber.
Gesehen am 02.04.2025